Solvent free enzymatic transesterification of crude jatropha oil in packed bed reactor - Veny, H.; Aroua, M.K.; Sulaiman, N.M.N. (2010)
In this study, we produce biodiesel from jatropha oil through enzymatic synthesis in a re circulated packed bed reactor (PBR). A solvent free system by three stepwise addition of one equivalent molar methanol in each step was chosen for this study. The enzyme was Lipozyme IM, a 1,3 regiospecific immobilized lipase from Mucor miehei. Initially, we scrutinized the appropriate amount of lipase by varied the lipase dosage from 5 to 20 based on Jatropha oil weight. Constant operating condition for all experiment was set to temperature of 45o C, PBR flow rate of 5 ml/min and 3 molar equivalent of methanol. The highest biodiesel yield of 54 was obtained at 10 of lipase dosage. We have also examined the effect of methanol addition time by conduct an experiment with one equivalent molar of methanol. The maximum conversion was found at 24 hours. However, a subsequent experiment carried out based on profile from those experiment, could only gave a biodiesel yield of 51. Afterwards, we observe the lipase stability in PBR solvent free system.